Effect of acute of short term exercise on rat circulating leukocytes and tissues lymphocytes - Dias, Rodrigo; Frollini, Anelena Bueno; Prestes, Jonato; Ferreira, Clílton Kraüss de Oliveira; Donatto, Felipe Fedrizzi; Verlengia, Rozangela; Palanch, Adrianne Christine; Cavaglieri, Cláudia Regina (Brazilian journal of physical education and sport, 2007)
Acute exercise sessions produce an immune system response, possibly leading to cessation, loss of continuity or performance decrement during the training period, caused by the increased upper respiratory infections (IVASs) susceptibility. Considering that lymphocyte cells have to fight infections and that sedentary subjects in poor physical condition should enroll physical programs of low intensity and volume, the aim of this study was to evaluate the amount of circulating leukocytes and lymphocytes as well as the mesenteric lymphocytes tissues, and the proliferative capacity of tissues lymphocytes in male Wistar rats submitted to acute sets of 5 and 15 minutes of low and moderate intensities. Results show leukocytosis and lymphocytosis in both groups 5 and 15 minutes of low and moderate intensities, increased tissue lymphocytes counting in the 5 minutes group of low intensity and in the 5 and 15 minutes groups of moderate intensity, in general, no alteration in the T cellular proliferative capacity, however with reduction in B lymphocytes in the 5 and 15 minutes groups of low intensity and in the 5 minutes of moderate intensity. The relevance and the clinical meaning of these alterations need to be well clarified for a better understanding of the complex triad: physical exercise, immunological responses and infections susceptibility after submaximal sets of short term.